PENGENALAN PROFIL PERUSAHAAN PERJALANAN PT. SMAILING TOUR BERBASIS MACROMEDIA FLASH MX - Septina Tri Wijayanti; Sutarno, SKom, MMSI Sutarno, SKom, MMSI (Jurnal Sistem Informasi, 2005)
Introduction to company profiles with Macromedia Flash MX application is to facilitatethe consumers know the products offered by PT. SMAILING TOUR, so that consumerscan use information in PT. SMAILING TOUR.With the system that are offered can make it easier to find information from both insideand outside the company.